Caboteur, vagabond et poète. L’Art de voyager de Jacques Lacarrière - Philippe Antoine (Viatica)
Jacques Lacarrière has published two travelogues. In Chemin faisant, he recounts his crossing of France on foot. In L’Été grec, he recalls his many stays in Greece. The author belongs to a family of writers who give pride of place to the experience of travel, without, however, relegating to the background a writing that results from patient formal and stylistic labor. He sees travel as an immersion in the natural and human environments he inhabits. Both a coaster and a wanderer, he takes a close-up view of the world, embracing slowness and rejecting the straight line. His travelogues unambiguously subscribe to the referential pact but are a literary recomposition of a lived experience revisited by memory and recreated by text, thanks to a language that stays as close to reality as possible and manages to enchant it.